Effect of solvent in the solvothermal synthesis of nickel(II)-terephthalate complex - Finisia, Yenni; Tjahjanto, Rachmat Triandi; Prananto, Yuniar Ponco (Acta Chimica Asiana, 2024)
This research aims to replace the use of dimethylformamide (DMF) with a greener solvent in the solvothermal synthesis of nickel(II)-terephthalate complex. Effect of solvent on the crystallinity degree, thermal stability, and band gap energy of the synthesized complex are also studied. The synthesis was carried out using solvothermal method at 150 0C for 10 hours with a Ni(II) : terephthalate acid mol ratio of 1:1 in several H2O:DMF solvent compositions (1:0; 1:1; and 0:1). The precipitated products underwent characterization using ATR-IR, P-XRD, SEM, TGA, Surface Area Analyzer, and UV-DRS. Findings revealed the successful formation of the Ni(II)-terephthalate complex using three different solvent compositions (H2O/DMF = 1:0, 1:1, and 0:1). This suggests that the complex can be synthesized using more environmentally friendly solvents, potentially reducing or substituting the use of DMF solvent. However, the solvent affects the characteristics of the synthesized complex, in which green block microcrystalline solid was obtained when using water as the solvent, meanwhile green aggregates with lower crystallinity degree was precipitated out when using DMF or H2O-DMF. The Ni(II)-terephthalate complexes obtained from the H2O and H2O-DMF solvents are different to that of from the DMF solvent, but they both has identical powder diffraction pattern with previously reported compound of [Ni3(OH)2(C8H4O4)2(H2O)4].2H2O. Furthermore, the use of water as the solvent increase the crystallinity degree and thermal stability of the complex but the band gap energy of the synthesized Ni(II)-terephthalate complex compared to that of obtained from the DMF solvents.